Changes of Neolithic subsistence in south Hangzhou Bay coast, eastern China: An adaptive strategy to landscape processes - Dai, Jinqi; Deng, Lanjie; Feng, Dan; Zhao, Xiaoshuang; Wang, Huimin; Li, Xueming; Xiao, Li; Zhang, Xiaoyu; Chen, Jing; Li, Maotian; Chen, Zhongyuan; Liu, Yan; et al. (Frontiers in Plant Science, 2022)
The transition from hunting and gathering to agricultural subsistence is a striking feature of the Neolithic revolution worldwide. Known as the cradle of a series of representative Neolithic cultures, south Hangzhou Bay (SHB) witnessed substantial changes in both landscape and human subsistence during the Holocene, yet the relationship between them was not well established. Here, we combined archaeobotanical results from sediment cores with archaeological findings to illustrate the subsistence changes during the Neolithic regime in the context of the landscape process in SHB. Our result showed that SHB was inundated by marine transgression 8,200 years ago without significant human imprints. At 8,200–7,600 cal yr. BP, the initial coastal wetland formation at locations with the semi-enclosed landscape would have facilitated the activities of hunting-gathering, incipient rice cultivation, and collecting seafood if accessible. Pollen and phytoliths evidence from multiple sediment cores in the Yaojiang Valley (YJV) suggested a desalinization process of wetland in the following hundreds of years. This amelioration of the environment had favored the intermittent rice cultivation at various locations in the YJV, where archaeological evidence was absent. Since 7,000–6,600 cal yr. BP, as freshwater wetland expanded with coastal progradation, a wide variety of food resources became available. Meanwhile, rice domestication began to serve as a crucial food supplement as evidenced by both microfossil results and archaeological findings. With the expansion of the coastal plain after 5,500 cal yr. BP, rice farming became widespread and rice consumption was increasingly important in the diet, as supported by discoveries of upgraded farming tools, abundant rice remains, and ancient rice paddies. Above all, the change of subsistence from hunting-gathering to rice farming exhibited an adaptive strategy in response to landscape evolution from an initial marine-influenced setting to a later coastal plain.